2021
DOI: 10.3390/d13020080
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Mites

Abstract: Nature is a highly complex, intricate system constructed of a network of interdependencies between individual species, their communities and their habitats. When climatic factors (such as temperature and humidity) and environmental factors (for example, latitude) are additionally considered, it comes as no surprise that scientists investigating this complicated and wondrous world face considerable problems. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Acari are a subclass of ubiquitous arachnids with a tiny body, generally less than 1 mm in length with tracheal or cutaneous breeding, and many of them are parasites of other animals or plants. Acari, also called "mites," inhabit both terrestrial and aquatic ecosystems and can even be found in relatively abundant amounts in aeroplankton [145]. Acari are one of the most diverse groups of arachnids on Earth, and about 60,000 species have been described [146].…”
Section: Acarimentioning
confidence: 99%
“…Acari are a subclass of ubiquitous arachnids with a tiny body, generally less than 1 mm in length with tracheal or cutaneous breeding, and many of them are parasites of other animals or plants. Acari, also called "mites," inhabit both terrestrial and aquatic ecosystems and can even be found in relatively abundant amounts in aeroplankton [145]. Acari are one of the most diverse groups of arachnids on Earth, and about 60,000 species have been described [146].…”
Section: Acarimentioning
confidence: 99%
“…Most species are understood to inhabit tropical regions (Walter et al 1998; Basset et al 2012, 2015; Stork 2018. Mites, which are fundamental contributors to global ecological functioning through their participation in energy, matter and information flows (Gwiazdowicz 2021), can be phytophagous, parasitic and predatory, and also consume algae, decaying organic material, detritus, fungi, lichens, microbes, mosses, nectar and pollen (Krantz 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Since ecosystems are highly complex with network of interdependencies and interactions among different species and their habitats, changing in climate factors affect natural flora and fauna. Therefore, mites with important role in this intricate ecological system are highly affected by ecological dynamics (Okabe et al, 2012;Gwiazdowicz, 2021). Heterostigmatic mites (Acari: Biodiversity and Systematics 2022  8 (1) Prostigmata) are classified in eight Superfamilies and include more than 2000 described species (Walter et al, 2009;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%